MEDIA SOSIAL SEBAGAI SARANA TRANSFORMASI PARTISIPASI POLITIK PEMUDA: STUDI SOSIOLOGIS PADA PEMILU DAN PILKADA TAHUN 2024 DI KABUPATEN TAPANULI UTARA - Sandra Ronauli Sihombing; Harisan Boni Firmando, Omta Purba; Elvri Teresia Simbolon, Wensdy Sitindaon (STKIP Subang, 2025)
This research aims to examine how social media as a new media platform contributes to shaping the political participation patterns of youth in North Tapanuli Regency, and to identify the factors that determine the level of digital political participation among young voters in the 2024 General and Regional Elections. This study employs a qualitative approach, using in-depth interviews and documentation as data collection techniques. The informants consist of 11 individuals, including ordinary youth, young political candidates, political figures, and youth involved in organizations. The findings reveal that social media has become an active participatory space for youth in the realm of local politics. Young people are not merely campaign targets, but also active agents in shaping public opinion, disseminating information, and even creating political content. The study highlights that the dominance of young voters and the widespread use of social media have led to a transformation in political campaign styles. This includes the emergence of cheerful campaign models, the use of local influencers, and more emotionally engaging political communication strategies. These transformations are influenced by technological adaptation, digital identity, and a growing desire among youth to participate informally in the democratic process. In conclusion, social media has proven to be a transformative force that reshapes youth political participation while simultaneously presenting new opportunities and challenges for local democratic life.